The Proposal for a Central Bank in the United States: A Critical View - Sprague, O. M. W. (Quarterly Journal of Economics, 1909)
Introduction: the success of existing central banks, 363.—Minor obstacles in the United States, 365.—The functions of central banks, 369.—I. The activities of central banks in normal times, 373.—The absence of branch banking an insuperable obstacle in the case of government deposits and the issue of notes, 380.—Credit notes a dangerous instrument, when the use of deposit credit is general, 386.—II. The precautionary stage in the policy of central banks, 388.—The sliding scale of discount would be ineffective in the United States, 393. —The kind of central bank which has been proposed for the United States is unlike those in Europe, because it would not be able to restrain credit expansion, 396.—III. Activities of central banks during crises: a central bank not needed to handle the foreign exchange situation, 400; or to insure the continuance of loans, 403.—The suspension of payments can be remedied without revolutionary changes in our present system, 407.—Conclusion, 413.